Journal of Orthopaedic Surgery and Research - Maffulli, Nicola; Furia, John
Journal of Orthopaedic Surgery and Research is an open access journal that encompasses all aspects of clinical and basic research studies related to musculoskeletal issues. Orthopaedic research is conducted at clinical and basic science levels. With the advancement of new technologies and the increasing expectation and demand from doctors and patients, we are witnessing an enormous growth in clinical orthopaedic research, particularly in the fields of traumatology, spinal surgery, joint replacement, sports medicine, musculoskeletal tumour management, hand microsurgery, foot and ankle surgery, paediatric orthopaedic, and orthopaedic rehabilitation. The involvement of basic science ranges from molecular, cellular, structural and functional perspectives to tissue engineering, gait analysis, automation and robotic surgery. Implant and biomaterial designs are new disciplines that complement clinical applications. JOSR encourages the publication of multidisciplinary research with collaboration amongst clinicians and scientists from different disciplines, which will be the trend in the coming decades.